The Structural design of language - Stroik, Thomas S.; Putnam, Michael T. (Cambridge University Press, 2013)
"One of the most important principles which underlies biolinguistics is that Turing's thesis must be satisfied: the structural design of biological systems obey physical and mathematical laws. Whilst much work has been done to identify the components of language, surprisingly little attention has been paid to examining and understanding the structural design of language itself, and how it satisfies Turing's thesis. The components of language must be somehow inter-structured to meet thresholds of simplicity, generality, naturalness and beauty, as well as of biological and conceptual necessity; but exactly how they do so has thus far been under-articulated. In this book, Stroik and Putnam investigate what this structure looks like, and argue that minimalist syntax has central importance. In so doing, radical new insights emerge into what the language faculty is, how language emerged in the species and how language is acquired by children"--Provided by publisher.